Why is reusable bag consumption easier to say than do? - Yan, Dongqing; Cai, Xiang; Xie, Meiying; Javeed, Sohail Ahmad; Liu, Fengqin; Cao, Qun (Frontiers in Psychology, 2022)
White pollution has become a global problem. China issued a strict plastic ban but fell into an awkward position. Despite the increasing environmental awareness, the positive attitude of consumers toward using reusable bags instead of plastic bags is difficult to reflect on from their behavior. This article bridges this gap by utilizing a consumer behavior framework based on the behavioral reasoning theory (BRT) and the attitude-behavior-context (ABC) model. This framework is tested using structural equation modeling with 481 Chinese consumers. This article confirms that the value has a significant impact on consumer attitudes. Meanwhile, the article reveals the positive influence of “reasons for” in predicting attitudes and the negative influence of “reasons against” in predicting intentions. Reusable bag consumption behavior is a result of multiple pathways working together, which causes the gap between attitudes and behaviors. This article also confirms the moderating role of the Chinese face and the enforcement of the plastic ban in influencing behavior. These findings offer interesting insights for enterprises and governments to solve the problem of plastic consumption.